Physiological traits and oxidative stress markers during acclimatization of micropropagated plants from two endangered Plantago species: P-algarbiensis Samp. and P-almogravensis Franco - Gonçalves, Sandra (2019)
Plantago algarbiensis Samp. and Plantago almogravensis Franco are species endemic to Portugal at risk of global extinction. The aim of this study was to investigate the ex vitro performance of micropropagated P. algarbiensis and P. almogravensis plants in terms of survival, relative water content (RWC), photosynthetic pigment contents, H2O2 accumulation, activities of superoxide dismutase (SOD) and catalase (CAT), lipid peroxidation, and soluble protein content, in comparison with wild-grown plants. Relatively high survival rates and RWC values during the acclimatization process were observed for both species. In P. algarbiensis, the pigment content increased when plantlets were transferred to ex vitro conditions, indicating enhanced light absorption capacity. No significant alterations in H2O2 content, CAT activity, or lipid peroxidation level were observed during acclimatization, but the protein content decreased in plants at the end of the growth chamber and greenhouse stages. When P. almogravensis plantlets were transferred to the ex vitro environment, decreases in the H2O2 content were observed that correlated to increased CAT activity and SOD maintenance, which lead to decreased lipid peroxidation and protein content. It was concluded that micropropagated P. algarbiensis and P. almogravensis plants were able to manage the oxidative stress induced by the in vitro environment and to perform well under ex vitro conditions.